Diversity and abundance of lepidopteran stem borer natural enemies in natural and cultivated habitats in Botswana - Mutamiswa, Reyard; Moeng, Eva; Le Ru, Bruno P.; Conlong, Des E.; Assefa, Yoseph; Goftishu, Muluken; Nyamukondiwa, Casper (Academic Press and Elsevier, 2022)
Lepidopteran stem-borers in Africa are attacked by diverse natural enemies in natural and cultivated environments. Field surveys of stem-borer natural enemies and associated host plants were conducted during the austral summers of 2014/15 and 2015/16 on natural and cultivated habitats across Botswana to determine their diversity and relative abundance. In cultivated habitats, the most common parasitoids of larvae were Cotesia flavipes Cameron, C. sesamiae (Cameron), and of pupae, Pediobius furvus Gahan and Gambroides nimbipennis Seyrig. In natural habitats, the larval parasitoids Chelonus curvimaculatus Cameron and Goniozus indicus Ashmead were recorded, along with the pupal parasitoid, Dentichasmias busseolae Heinrich. Furthermore, the predatory ants Linepithema humile Mayr, Crematogaster peringueyi Emery and Aenictus species were recorded in both cultivated and natural habitats. The major cultivated plants hosting stem-borers and related natural enemies were maize, sorghum, sweet sorghum, and the major wild plants were Echinochloa pyramidalis, Typha latifolia, Schoenoplectus corymbosus and Cyperus dives. Chilo partellus Swinhoe and Sesamia spp. were the major hosts for parasitoids, with C. partellus predominating in cultivated habitats and Sesamia jansei Tams & Bowden in natural habitats. Larval parasitism ranged from 2.1 to 34.7% and 3.3 to 14.3% in cultivated and natural habitats respectively, whereas pupal parasitism ranged from 6.1 to 10.6% and 6.7 to 9.1%, respectively. Parasitoid percentage abundance ranged from 1.1 to 41.6% and 4.8 to 38.1% in cultivated and natural habitats respectively, with C. flavipes dominating in cultivated and C. curvimaculatus in natural habitats. Our results show that cultivated and natural environments in Botswana harbor a diverse natural enemy community worthy of conserving for stem-borer biological control.